2013
DOI: 10.1186/1471-2148-13-151
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon divergence and reproductive isolation in Timema stick insects

Abstract: BackgroundIndividuals commonly prefer certain trait values over others when choosing their mates. If such preferences diverge between populations, they can generate behavioral reproductive isolation and thereby contribute to speciation. Reproductive isolation in insects often involves chemical communication, and cuticular hydrocarbons, in particular, serve as mate recognition signals in many species. We combined data on female cuticular hydrocarbons, interspecific mating propensity, and phylogenetics to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…Our results identify both pre-and postcopulatory mechanisms of sexual selection as contributing to the evolution of posterior lobe morphology. Our results also lend some support the idea that sexual selection on genital morphology could contribute to the evolution of reproductive isolation between populations, similar to what is observed from sexual selection on other traits (Phelan and Baker 1987;Boughman 2001;Svedin et al 2008;Head et al 2013;Manier et al 2013b;Schwander et al 2013;Seddon et al 2013;Wojcieszek and Simmons 2013;Castillo and Moyle 2014;Dyer et al 2014;Hudson and Price 2014;Latour et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Our results identify both pre-and postcopulatory mechanisms of sexual selection as contributing to the evolution of posterior lobe morphology. Our results also lend some support the idea that sexual selection on genital morphology could contribute to the evolution of reproductive isolation between populations, similar to what is observed from sexual selection on other traits (Phelan and Baker 1987;Boughman 2001;Svedin et al 2008;Head et al 2013;Manier et al 2013b;Schwander et al 2013;Seddon et al 2013;Wojcieszek and Simmons 2013;Castillo and Moyle 2014;Dyer et al 2014;Hudson and Price 2014;Latour et al 2014).…”
Section: Discussionsupporting
confidence: 86%
“…; Schwander et al. ), roles in waterproofing and transcuticular water loss (Gibbs and Pomonis ; Gibbs and Rajpurohit ), and sensitivity to biotic and abiotic factors. As pheromones, these molecules are involved in species and sex‐specific recognition (Singer ) and mating status (Everaerts et al.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of cuticular hydrocarbons (CHCs) serving as contact pheromones in insects have revealed a wealth of information concerning their biosynthesis (Schal et al 1998;Howard and Blomquist 2005), regulation by a handful of genes (Dallerac et al 2000;Gleason et al 2005), diversity in closely related species (Page et al 1997;Oliveira et al 2011;Schwander et al 2013), roles in waterproofing and transcuticular water loss (Gibbs and Pomonis 1995;Gibbs and Rajpurohit 2010), and sensitivity to biotic and abiotic factors. As pheromones, these molecules are involved in species and sex-specific recognition (Singer 1998) and mating status (Everaerts et al 2010) during courtship and have been shown to mediate female preference by sexual selection Havens and Etges 2013) and sexual isolation (Coyne and Charlesworth 1997;Etges and Ahrens 2001;Ishii et al 2001;Dopman et al 2004;Peterson et al 2007) between populations and species.…”
Section: Introductionmentioning
confidence: 99%
“…The Timema host phylogeny is very robust (Schwander et al. , ). For the parasite phylogeny, although several nodes are weakly supported, topology errors for the weakly supported nodes would not influence the main result.…”
Section: Discussionmentioning
confidence: 99%
“…Both TreeMap 3.0b and Jane 4.0 use the phylogenies of hosts and their parasites as input. To perform the cophylogenetic analyses implemented in TreeMap 3.0b, we used a robust, previously published Timema phylogeny (Schwander et al 2011(Schwander et al , 2013, which includes host species for which we did not find any parasites during 9 years of sampling. Because hosts without associated parasites cannot be used in Jane 4.0, we pruned the host phylogeny to comprise only the nine Timema species for which we found parasites in analyses with Jane 4.0.…”
Section: Host-parasite Cophylogenetic Analysesmentioning
confidence: 99%